Location-specific integrated farming system models for resource recycling and livelihood security for smallholders - Kumar, Sanjeev; Shivani,; Dey, Amitav; Kumar, Ujjwal; Kumar, Rakesh; Mondal, Surajit; Kumar, Ajay; Manibhushan, (Frontiers in Agronomy, 2022)
The present investigation was carried out in a holistic mode to study the interactions among the integrated farming system (IFS) components and to develop and design a sustainable IFS model which is technologically sound, economically viable, environmentally benign and socially acceptable for middle Indo-Gangetic Plains. For efficient utilization of farm resources and to enhance the income per unit area of land, 10- IFS models have been developed at the farmers’ fields of Patna, Nalanda and Vaishali district of Bihar, India during 2016-21, involving the components like crops, poultry, cattle, goat, mushroom farming, fishery and duckery in different combinations. Out of ten different integrations, three primary cropping systems prevailing in the state were undertaken and seven other components were integrated in a synergistic mode. Each system was allocated an area of 0.8 ha (2000 m²) viz. (i) Rice-wheat, (ii) Rice-maize, (iii) Rice-maize-moong (crop), (iv) crop+vegetable+goat, (v) crop+fish+goat, (vi) crop+fish+cattle, (vii) crop+fish+duck+goat, (viii) crop+fish+duck, (ix) crop+fish+mushroom and (x) crop+fish+poultry. To sustain the productivity of soil health, inorganic fertilizers combined with organic wastes, obtained from various components of IFS viz. recycled pond silts, poultry manure, duck manure, goat manure and cow dung as farmyard manures (FYM), composted residues and vermicompost were applied to crops grown under different IFS models. Nutrient content of manure increased manifolds after recycling as compost and vermicompost. Residue recycling revealed that integration of crops with fish and duck resulted in higher fish productivity and higher net returns (increased by USD13) in comparison to poultry dropping fed fishes. Due to the recycling of droppings viz. poultry, duck, goat, cattle and plant wastes, an additional quantity of 56.5 kg N, 39.6 kg P2O5 and 42.7 kg K2O were added to the soil during the study. Crop integrated with fish+duck+goat had the maximum rice grain equivalent yield (RGEY), net returns and employment opportunity (467 man-days/year) from 0.8 ha land, followed by crop+fish+poultry integration. The sustainability index (0.77) and net energy gain (95770 MJ) were also found highest with crop+fish+duck+goat integration indicating the optimum efficiency of all the farming system integrations for the region.